Penguatan Literasi Bahasa Inggris Siswa/I TK melalui Kegiatan Instruksional Pembuatan Salad Buah - Muhammad Muslim Nasution; Soraya Grabiella Dinamika; Yoni Rahayu; Yurial Arief Lubis (Yayasan Literasi Sains Indonesia, 2025)
This community service activity aims to strengthen English literacy in early childhood through instructional activities involving fruit salad making at the Chalisaturahmi Luqman Hakim Foundation in Medan. Participants consisted of 12 kindergarten students and 6 accompanying parents. The method used was participatory learning with a learning by doing approach, covering the stages of preparation, implementation, evaluation, and follow-up. Children were introduced to basic English vocabulary related to fruit names, colours, flavours, and simple instructions through the direct practice of making fruit salad. The pre-test and post-test evaluations showed an increase in English literacy skills with an average N-gain score of 0.6 (moderate category). Although the improvement was at a moderate level, this activity was able to foster enthusiasm in children, improve fine motor skills, build self-confidence, and maintain healthy living habits. This program also involved teachers and parents so that it could be continued at school and at home. Thus, this activity is relevant to support foreign language proficiency from an early age, in line with a curriculum that emphasizes active, creative, and fun learning, as well as being a model of contextual learning that can be replicated at various levels of education.